Analysis of Environmental and Social Factors in the Dynamics of Arboviruses in Bahia: A Methodological Proposal - Elias Reis da Silva; Filipe Cardoso Brito; Toni Alex Reis Borges; Aloísio Santos Nascimento Filho; Hugo Saba (JOURNAL OF BIOENGINEERING, TECHNOLOGIES AND HEALTH, 2026)
Arboviruses represent a significant challenge to public health, requiring a careful analysis of the environmental factors that impact their propagation. This research project mapped the relationships between epidemiological, climatic, and environmental data for the development of more effective public policies. The methodology adopted was based on experimental research and followed an iterative and incremental path, divided into stages ranging from data collection to the analysis and interpretation of the results found. The results include the development of a model of the relationships between variables and the analysis of the patterns found.